Quantitative, Label-Free Detection of the Aggregation of α-Synuclein Using Microcantilever Arrays Operated in a Liquid Environment. (19th October 2011) - Jensen, Jason; Farina, Margherita; Zuccheri, Giampaolo; Grange, Wilfried; Hegner, Martin
Abstract : Early detection of protein aggregation is of great importance in the field of neurodegenerative diseases. The successful detection of the aggregation of the protein α -synuclein in a quantitative, label-free manner by functionalising a microcantilever with α -synuclein monomers and operating it in dynamic mode in the presence of α -synuclein monomers in solution is reported. A total mass of 6 ng of α -synuclein was detected over 9 hours on the surface of the cantilever. The result is compared to conventional fluorescence measurements of α -synuclein aggregation under similar conditions. It is found that the label-free cantilever detection method requires a concentration of protein 50 times smaller than that of the current method and indicated potential for significantly faster response times.